Rancang Bangun Sistem Manajemen Nilai Siswa Menggunakan PHP dan MySQL - Maulana Al Nouri; M. Rafiif Albani; M. Hafif Naibaho; Arung Buana Subuh (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2025)
This study aims to design and develop a web-based student score sorting system by applying a sorting algorithm to improve the effectiveness and efficiency of academic data processing. The research employs a Research and Development (R&D) approach using the Waterfall development model, which includes the stages of requirements analysis, system design, implementation, and testing. The system was developed using the PHP programming language and a MySQL database. The score sorting process was implemented by integrating a sorting algorithm into the system to automatically arrange student data based on specific criteria. The system successfully achieved 100% accuracy in sorting student scores and demonstrated stable time efficiency across various data sizes. Therefore, this system can assist teachers and schools in managing student score data quickly, accurately, and in a well-structured manner.